Phytochemical And Proximate Compositions of Tetracarpidium Conophorum [African Walnut] Seeds. - Chikezie, Uchechukwu; Yvonne, Nkeiruka (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2018)
A sample of boiled Tetracarpidiumconophorum (African walnut) seeds was analyzed for the phytochemical and proximate compositions. The result of the phytochemical [qualitative] screeningrevealed the presence of high concentrations of Alkaloids and Steroids, and moderate concentration of Tannins. There were no traces of Saponins, Phlobotannins, Flavonoids, Phenols and Glycosides. The proximate analysis showed that the boiled seeds contained 5.5% moisture, 19.3% carbohydrate, 17.9% protein, 53.4% crude fat, 1.24% crude fiberand 2.67% ash. Data from thisstudy showedthat theboiled Tetracarpidiumconophorum seeds contain some bioactive compounds and have good nutritional composition. They could be useful in pharmaceutical formulations and as food.